1995
DOI: 10.1159/000244142
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal and Pancreatic Hormones in the Human Fetus and Mother at 18–21 Weeks of Gestation

Abstract: Several gastrointestinal hormones appear to play an important developmental role in the newborn, particularly in preterm neonates. Although the cells producing these peptides develop towards the end of the first trimester, fetal secretion of these regulatory peptides has not hitherto been demonstrated. Using samples collected by fetoscopy at 19–21 weeks of gestation we have measured concentrations of several gastrointestinal and pancreatic hormones. Maternal venous and amniotic fluid hormone concentrations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…High surges of glucocorticoids have the ability to elicit precocious maturation in a number of experimental animal models (5,43). Signals derived from luminal amniotic fluid may also contribute to the development of enzyme activities in utero (44), possibly mediated by specific growth factors. Organ culture studies of human fetal intestine in defined tissue culture medium have demonstrated differential effects of hydrocortisone, insulin, and epidermal growth factor in regulating hydrolase expression, apolipoprotein and lipoprotein secretion, and cellular proliferation (45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…High surges of glucocorticoids have the ability to elicit precocious maturation in a number of experimental animal models (5,43). Signals derived from luminal amniotic fluid may also contribute to the development of enzyme activities in utero (44), possibly mediated by specific growth factors. Organ culture studies of human fetal intestine in defined tissue culture medium have demonstrated differential effects of hydrocortisone, insulin, and epidermal growth factor in regulating hydrolase expression, apolipoprotein and lipoprotein secretion, and cellular proliferation (45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is also presumed to play a role in the developmental process of fetus (5, 10). Components of human amniotic fluid such as growth factors and hormones are important mediators of the functional gastrointestinal development (38). They can be transported across the fetal epithelium by endocytic process (39).…”
Section: Potential Functional Implicationsmentioning
confidence: 99%
“…Both GLP-1 and GIP are gut-derived incretin hormones that stimulate insulin and suppress glucagon secretion, inhibit gastric emptying, and reduce appetite and food intake (28). Placental transfer of both incretin hormones might be considered negligible (29), and both hormones are secreted in the fetus (30)(31)(32)(33). Eating provokes the secretion of multiple gastrointestinal hormones involved in the regulation of gut motility, secretion of gastric acid and pancreatic enzymes, gall bladder contraction, and nutrient absorption as well as insulin secretion.…”
Section: Discussionmentioning
confidence: 99%